2014
DOI: 10.4040/jkan.2014.44.1.41
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Adult Korean Children Caring for Parents Institutionalized with Dementia

Abstract: 연구의 필요성만성질환이나Purpose: The purpose of the study was to explore and describe the experience of adult Korean children who are caregivers for parents institutionalized with dementia. Methods: Participants were fourteen adult children caregivers of elders institutionalized with dementia. Data were collected through in-depth unstructured interviews with individual participants from August to November, 2012. Theoretical sampling was used to the point of theoretical saturation. Data were analyzed using Strauss and Cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 17 publications
1
16
0
2
Order By: Relevance
“…With such a heavy caregiving burden, families reach their limit in caring for older adults at home [9]. As a result, despite the negative perception of institutionalizing [5], the admission of older adults to nursing homes (NHs) has consistently risen, reaching 345,000 users of NHs in Korea in 2016 [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With such a heavy caregiving burden, families reach their limit in caring for older adults at home [9]. As a result, despite the negative perception of institutionalizing [5], the admission of older adults to nursing homes (NHs) has consistently risen, reaching 345,000 users of NHs in Korea in 2016 [6].…”
Section: Introductionmentioning
confidence: 99%
“…The common belief is that families' caregiving burdens would be diminished by admitting their relatives to NHs, however, families of older adult NH residents still experience different aspects of the caregiving burden [10], such as guilt, confusion with their caregiving role, and role conflicts with NH staff [9,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies assessing the quality of life of caregivers providing for those with dementia found that they experience high levels of grief, ambivalence and some psychological problems (Kwon & Tae , Skaalvik et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly among acute and subacute stroke patients, those with moderate to severe impairment have to depend on others to accomplish most of their activities of daily living and such roles are csarried out by their main caregivers [ 2 ]. Such care has usually been performed by the family, but care by professional caregivers is now being widely used in response to the structural change of Korean society resulting from the increasing life expectancy and elderly population [ 10 , 11 ]. Therefore, in this study, we investigated the type of caregiver (family or professional caregiver) and their effect in stroke patients' depression.…”
Section: Introductionmentioning
confidence: 99%